Recovery and Identification of Pathogenic Fungi of Bee Colonies (Apis Mellifera) and Study Their Ability to Produce Extracellular Enzymes - Al-Asadi, Rasheed O.; Shaban, Abbas D. (American Journal of Biology and Natural Sciences, 2026)
The current study of enzymatic characteristics of Aspergillus flavus and Aspergillus niger associated with honeybee workers in Iraq regarding these hydrolytic enzymes as major biochemical markers of their pathogenicity. Fungi samples were obtained from 1 st October to 1 st December, 2025, in each of eight ecological zones in Basrah, Dhi Qar and Diyala. Statistical analysis of the fungi distribution showed that the Al-Zubayr district had the greatest overall number frequency of isolates, presenting together both species simultaneously in hives sampled and followed by the Al-Qurna district who displayed a co-present therapeutic effect to tackle against both pathogens. Four essential extracellular enzymes, which included. ; Proteolytic Enzymes: Lipolytic Enzymes: Chitin-degrading Enzymes: Phenoloxidases, were screened qualitatively using specific selective mediums The findings revealed that the production rate of these enzymes was universally (100) positive in all the isolates tested, and AF-4 strain proved to be an The findings revealed that the production of these enzymes was universally positive (100%) across all tested isolates. Specifically, the FA-4 strain exhibited high enzymatic proficiency on the selective media.These results emphasize a complex and strong set of enzymes in local Iraqi strains that are effectively used to break down honeybee tissues and provide potent clinical progression of Stonebrood disease in local apiaries.